Analisis motif pembelian dan profil perilaku ”green product customer” (Studi Pada Konsumen Produk Pangan Organik di Purwokerto) - Weni Novandari (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2011)
ABSTRACT Aims of this research are to get a better understanding about green product customer profile and their motives to purchase green products. This research also analyzes the effect of environment consciousness, customer involvement with environmental issues, and willingness to pay at the premium prices on customer’s intention to buy green product. Questionnaires were distributed to organic food customer in Purwokerto. 108 completed questionnaires were used in the analysis. The data was then analyzed using descriptive analysis and Partial Least Square as an analysis tools. The result shows that consumers were becoming more concerned about their consumption and the impact on the environment, especially for their health. The results from PLS analysis indicate that environment consciousness, customer involvement with environmental issues and willingness to pay at the premium prices has a significant relationship on customer’s intention to buy green product.The idea implied in this research will be much help in resolving problem and decision making, connected to reinforce the green product purchasing Keywords :  customer profile, motives to purchase, environment consciousness, customer involvement with environmental issues, willingness to pay at the premium prices, customer’s intention to buy green product